2017
DOI: 10.1590/0004-282x20170110
|View full text |Cite
|
Sign up to set email alerts
|

Alzheimer’s disease and cytokine IL-10 gene polymorphisms: is there an association?

Abstract: Alzheimer’s disease (AD) is the most common form of dementia. In the last 15 years, a new theory has proposed the autoimmune mechanism as a trigger for AD. Studies on the association between AD and inflammatory biomarkers have yielded controversial results. Interleukin-10 (IL-10), an anti-inflammatory mediator, has been pointed out as one of the main cytokines associated with the occurrence of AD. Moreover, treatment that increases IL-10 levels could be a potential therapy for AD, since this cytokine acts on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…In fact, the production of IL-10 is one of the most important mechanisms to counteract neuronal damage driven by excessive inflammation. Meanwhile, the decreased level of IL-10 has been reported to contribute to the neuroinflammatory process, which favors the development of neurodegenerative diseases including AD [42]. Our findings demonstrated that HSR1101 exerts anti-inflammatory action through both inhibiting pro-inflammatory mediators and inducing anti-inflammatory cytokine(s), suggesting a critical role of the hydroxyl moiety at the R1 position ( Figure 1).…”
Section: Discussionmentioning
confidence: 63%
“…In fact, the production of IL-10 is one of the most important mechanisms to counteract neuronal damage driven by excessive inflammation. Meanwhile, the decreased level of IL-10 has been reported to contribute to the neuroinflammatory process, which favors the development of neurodegenerative diseases including AD [42]. Our findings demonstrated that HSR1101 exerts anti-inflammatory action through both inhibiting pro-inflammatory mediators and inducing anti-inflammatory cytokine(s), suggesting a critical role of the hydroxyl moiety at the R1 position ( Figure 1).…”
Section: Discussionmentioning
confidence: 63%
“…These SNPs control the transcription of IL-10 mRNA and IL-10 protein expression in vitro [13]. To date, several studies have exhibited associations between -592C/A, −819C/T and -1082A/G promoter SNPs with susceptibility to aging [14], risk of cancer [15][16][17], schizophrenia [18], Alzheimer's disease [19][20][21][22][23], acute myocardial infarction (AMI) [24] and inflammatory bowel disease (IBD) [25]. Researchers have indicated that IL-10 -592C/A and -819C/T SNPs can be predictive factors for the pathogenesis of POAG in the Chinese population [26].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the findings of the sixteen studies from around the world were conflicting 6 and a recent meta-analysis did not find a significant association between -1082G>A in IL-10 and AD risk 8 , interestingly both studies conducted in Brazil showed associations between IL-10 polymorphisms and AD 9 or cognitive impairment 10 . The discrepancies across studies might be due to numerous causes, such as different sample sizes, unaccounted factors that modify IL-10 expression, and/or the fact that studies were performed in different populations.…”
Section: In This Context Magalhães and Colleaguesmentioning
confidence: 96%
“…Anti-inflammatory cytokines, such as interleukin-10 (IL-10), have also been studied in AD, particularly because the modulation of inflammatory processes might be a target for the disease treatment. Its exact role on the neurodegenerative processes, however, still needs more clarification; in transgenic animal studies, IL-10 has shown beneficial effects on cognition in some studies, but more recent research has indicated that IL-10 might worsen Aβ accumulation by inhibiting microglial phagocytosis 6,7 . Overall, the data currently available indicate that modulation of the inflammatory response in the early stages of the disease rather than an anti-inflammatory only approach might be a better treatment strategy for AD 3,6 .…”
mentioning
confidence: 99%